2022
DOI: 10.2903/j.efsa.2022.7408
|View full text |Cite
|
Sign up to set email alerts
|

Update of the list of QPS‐recommended microbiological agents intentionally added to food or feed as notified to EFSA 16: suitability of taxonomic units notified to EFSA until March 2022

Abstract: The qualified presumption of safety (QPS) approach was developed to provide a regularly updated generic pre‐evaluation of the safety of microorganisms, intended for use in the food or feed chains, to support the work of EFSA's Scientific Panels. The QPS approach is based on an assessment of published data for each agent, with respect to its taxonomic identity, the body of relevant knowledge, safety concerns and occurrence of antimicrobial resistance. Safety concerns identified for a taxonomic unit (TU) are, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 123 publications
0
15
0
Order By: Relevance
“…LAB, which are human intestinal symbiotic bacteria, have long been used in the production of fermented foods through lactic acid fermentation. As such, many LAB are generally recognized as safe by the US Food and Drug Administration [ 21 ] and given the qualified presumption of safety status by the European Food Safety Authority [ 22 ]. LAB, which do not produce endotoxins like those produced by E. coli , have certain advantages as expression hosts for recombinant proteins and are therefore an attractive platform, especially in the context of in vivo administration [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…LAB, which are human intestinal symbiotic bacteria, have long been used in the production of fermented foods through lactic acid fermentation. As such, many LAB are generally recognized as safe by the US Food and Drug Administration [ 21 ] and given the qualified presumption of safety status by the European Food Safety Authority [ 22 ]. LAB, which do not produce endotoxins like those produced by E. coli , have certain advantages as expression hosts for recombinant proteins and are therefore an attractive platform, especially in the context of in vivo administration [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The qualification ‘absence of aminoglycoside production ability’ was withdrawn for Bacillus velezensis based on recent information that did not support possible aminoglycoside production, thereby contradicting the original data on which the qualification was based (EFSA BIOHAZ Panel, 2023).…”
Section: Assessmentmentioning
confidence: 99%
“…lactis and concluded that there was no new information that would require a modification of the subspecies’ qualified presumption of safety status. 11 …”
Section: Acute Risksmentioning
confidence: 99%
“… 6–10 A foundational initiative by the European Food Safety Authority established the Qualified Presumption of Safety approach for live microorganisms used in foods. 11 This guidance is useful for recognizing microbial species with a history of safe use in foods. Pariza and colleagues 12 proposed a 15-step decision tree to guide safety evaluations for products that lack an established history of safe use.…”
Section: Introductionmentioning
confidence: 99%